Prevention Of Bullying At Sdn 02 Krajankulon Through Anti-Bullying Socialization - Arinda Avrilia Putri; M. Aqil Alwan; Devi Permata Sari; Dina Salsa Bila; Indah Robiah Rohmah; Nurkholis Majid; Ninik Faiqotul Jannah; Risma Amalia Putri; Zuanita Adriyani (Universitas Palangka Raya, 2024)
Bullying is a form of violence that occurs among children. Bullying is a form of violent behavior that involves the power to hurt an individual or a group verbally, physically, or psychologically. The impact experienced by bullying victims includes various mental health issues and physical health complaints. This research uses a phenomenological research method. This method is used to describe a person's experience of a phenomenon. Research results indicate that bullying remains a significant issue, particularly in verbal and physical forms. Therefore, the 18th KKN MIT team at post 109 UIN Walisongo Semarang held an anti-bullying socialization event focused on raising students' awareness about the negative impacts of bullying and providing an understanding of the importance of creating positive social relationships